Ewing tumor: a descriptive study of the cases seen at INCA/Hospital do Câncer - From 1986 to 1994 - Meohas, Walter (2022)
We studied 63 patients with a diagnosis of Ewing 's Sarcoma who were treated at the Brazilian National Cancer Institute (INCA) between 1986 and 1994. There were 37 male (59%) and 26 (41%) female patients. It affected mainly Young people: 92% (58patients) were under 30 years old with an average (mean) age of 19 years. Regarding race of race, 47 (75%) were caucasians, 13 (21%) were non caucasians and 3 (4%) were black.